Role of Terracing and Reforestation Efforts on Improving Soil Properties in Degraded Steep Lands - Mehmet Özalp; Ferit Dehşet; Bülent Turgut; Saim Yıldırımer; Eren İnanlı (Doğal Afetler ve Çevre Dergisi)
Serious land degradation have been occurring during the building of new roads associated with the construction of Deriner Dam, one of 15 large dams planned by the General Directorate of State Hydraulic Affairs and implemented within the Coruh Dam Projects. In this study, whether terracing and planting of seedling efforts in degraded areas as a result of building new roads within erosion control and reforestation efforts have any effect on improving soil characteristics were investigated. In accordance with this purpose, parameters including soil texture, pH, organic matter, total nitrogen, total lime, and electrical conductivity were determined for 45 soil samples taken from three different areas; two of which were erosion control areas where terraces built and planted with acacia and yellow pine seedlings, along an undisturbed (control) area with natural forests. After evaluating statistical analyses run on the soils data, it was determined that the reforestation efforts have resulted in improvements of soil properties at some degree but when they are compared to the soils of the undisturbed natural forest, it is clear that the degree of improvement is not sufficient yet. For example, while the organic matter of 3.71% and pH of 7.69 were determined for the forest area, same parameters were found as 1.13% and 7.99 for the acacia and 0.86% and 7.93 for the yellow pine areas, respectively.